PENDIDIKAN KEWARGANEGARAAN DI ERA DIGITALISASI 5.0: MEMBENTUK KARAKTER SISWA DI SEKOLAH DASAR - Saryono, Saryono (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
Civic education is highly crucial in elementary schools because technology has entered the era of 5.0 digitalization, demanding that the younger generation possess a profound understanding of civic values and the ability to adapt to rapid global changes. This article aims to investigate the importance of civic education for elementary school students. The methodology employed in this article involves the use of literature review, encompassing data collection from various literary sources, reading, note-taking, and processing relevant references related to the issues under study. The research findings indicate that civic education in elementary schools prepares students to become good citizens, possessing strong character, tolerance, and critical thinking skills, thereby enabling them to actively contribute to building an inclusive and dynamic society. This implies that education significantly contributes to shaping citizens with high morality, strong character, and the ability to compete globally in today's complex contemporary era.